Determination of Optimal Cost Electrical Charge Storage System in off — Grid Solar Illumination Systems. Issue 5 (September 2013) - Sharan, Anand
In this paper, a unit is developed for lighting homes and workplaces in many parts of the world where the electricity supply is not through grids. This unit consumes minimal energy and is available at an optimal cost. This minimal consumption system uses newly developed white light or Light Emitting Diodes (LEDs). These types of diodes have p- n junction and the voltage drop across the junction is around 3 Volts. So the batteries used in such illumination devices also have approximately 3 Volts. The utility of such devices (LED based) has increased in recent times because these are replacing kerosene lanterns in many countries around the world. The governments in such countries are reducing or eliminating the subsidies on kerosene, diesel etc (fossil fuels) due to a continued high price of crude oil. The challenge with the 3 Volt batteries is that their ratio of cost / total charge holding capacity is very high. They also pose problems with their disposal and repair. Moreover, many of these batteries are reported to explode while being charged. The present research work then replaces 3 Volt batteries with 12 Volt batteries which are commonly used and the ratio mentioned above - is low or minimal.